1984
DOI: 10.1002/prac.19843260202
|View full text |Cite
|
Sign up to set email alerts
|

Photochemie von Aminoketonen. V. Diastereoselektive Synthese von 3‐Aryl‐azetidin‐3‐olen durch Photocyclisierung von Aryl‐α‐amidoalkyl‐ketonen

Abstract: Photochemistry of Aminoketones. V. Diastereoselective Synthesis of 3‐Aryl‐azetidin‐3‐ols via Photocyclization of Aryl‐α‐amidoalkyl‐ketones N‐Acyl‐azetidin‐3‐ols 3 and 4 are formed by diastereoselective cyclization of n,π*‐excited N‐benzyl‐N‐phenacyl‐amides 1 and 2 in ether solution. Dependent on the nature of the p‐and α‐substituents of the phenacyl part and especially of the N‐acylgroups in the amides 1 and 2 competing reactions occur, particularly the NORRISH II cleavage and an oxydative cleavage of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Normally, the irradiation of such ketones gives a considerable amount of Norrish-Type-II cleavage products, and often the cleavage dominates the cyclization [16]. On the other hand, it was observed that the introduction of a heteroatom into the side chain of the ketone increases the cyclization yield [8] [17]. This effect can be explained by the conjugation of a heteroatom lone pair with the adjacent radical centre (see B in Fig.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Normally, the irradiation of such ketones gives a considerable amount of Norrish-Type-II cleavage products, and often the cleavage dominates the cyclization [16]. On the other hand, it was observed that the introduction of a heteroatom into the side chain of the ketone increases the cyclization yield [8] [17]. This effect can be explained by the conjugation of a heteroatom lone pair with the adjacent radical centre (see B in Fig.…”
Section: Methodsmentioning
confidence: 92%
“…Compound 5 was prepared in analogy to the procedure described by Fuhrmann et al [8] 1,1,2-trimethylpropyl)silyloxymethyl]-3-methoxy-3-phenylazetidin-3-ol (17 and ent-17, resp.) NaH (80%, 0.14 g, 1 equiv.)…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation